Teachers’ Profile on Minimum Competency Assessment Tasks Implementation in Senior High School Level - Afi Ni'amah (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2022)
Pandemic era has given amendment toward education that the government legalizes new regulation related to learning quality by considering assessment matter. In relation to assessment, minimum competency assessment is the first aspect to be deliberated. It made the society is not prepared and get incomprehensible. Considering teachers take essential role in the implementation of the new regulation, investigation on teachers’ competence on designing minimum competency assessment task comes into concern. In analyzing teachers’ competence, qualitative method was prepared by combining documentation and questionnaire. The documentation is minimum competency assessment tasks designed by teachers. The tasks designed were analyzed by using components of AKM. Based on the data analysis, the tasks designed were fulfilled and completed the components of AKM that teachers’ competence on designing AKM tasks is accomplished. In finding teachers’ sketch, questionnaire was then distributed. The questionnaire confirms teachers’ motivation in AKM implementation. By referring to the questionnaire, suggestion for further research related to minimum competency assessment is recommended for the sake of society’s conception on succeeding learning quality as well as assessment matter supplemented that support their perplexing.